Effects of short‐term cognitive‐coping therapy on resting‐state brain function in obsessive‐compulsive disorder - Jian‐Dong Ma; Chang‐Hong Wang; Ping Huang; Xunan Wang; Li‐Jing Shi; Heng‐Fen Li; De‐En Sang; Shao‐Jie Kou; Zhi‐Rong Li; Hong‐Zeng Zhao; Hong‐Kai Lian; Xian‐Zhang Hu (Brain and Behavior, 2021)
Abstract Background Obsessive‐compulsive disorder (OCD) tends to be treatment refractory. Recently, cognitive‐coping therapy (CCT) for OCD is reported to be an efficacious psychotherapy. However, the underlying neurophysiological mechanism remains unknown. Here, the effects of CCT on OCD and the resting‐state brain function were investigated. Methods Fifty‐nine OCD patients underwent CCT, pharmacotherapy plus CCT (pCCT), or pharmacotherapy. Before and after a 4‐week treatment, Yale‐Brown obsessive‐compulsive scale (Y‐BOCS) was evaluated and resting‐state functional magnetic resonance imaging (rs‐fMRI) was scanned. Results Compared with the baseline, significant reduction of Y‐BOCS scores was found after four‐week treatment (p < .001) in groups of CCT and pCCT, not in pharmacotherapy. Post‐treatment Y‐BOCS scores of CCT group and pCCT group were not different, but significantly lower than that of pharmacotherapy group (p < .001). Compared with pretreatment, two clusters of brain regions with significant change in amplitude of low‐frequency fluctuation (ALFF) were obtained in those who treated with CCT and pCCT, but not in those who received pharmacotherapy. The ALFF in cluster 1 (insula, putamen, and postcentral gyrus in left cerebrum) was decreased, while the ALFF in cluster 2 (occipital medial gyrus, occipital inferior gyrus, and lingual gyrus in right hemisphere) was increased after treatment (corrected p < .05). The changes of ALFF were correlated with the reduction of Y‐BOCS score and were greater in remission than in nonremission. The reduction of the fear of negative events was correlated to the changes of ALFF of clusters and the reduction of Y‐BOCS score. Conclusions The effectiveness of CCT for OCD was related to the alteration of resting‐state brain function—the brain plasticity. Trial Registration ChiCTR‐IPC‐15005969.